Cationic Dialdehyde Nanocellulose from Sugarcane Bagasse for Efficient Chromium(VI) Removal - Huang, Xiangyu; Dognani, Guilherme [UNESP]; Hadi, Pejman; Yang, Mengying; Job, Aldo E. [UNESP]; Hsiao, Benjamin S. (Amer Chemical Soc, 2020)
Cellulose-based materials are the most widely used green materials because of their abundance, sustainability, biodegradability, and functionalizability. The capability of cellulosic materials as adsorbents and coagulants to remove negatively charged contaminants from water requires the possession of a positively charged functionality. In this study, cationic dialdehyde cellulose (c-DAC) nanofibers with three different degrees of oxidation were created by preparing metaperiodate-oxidized cellulose followed by cationization using Girard's reagent T. The resulting c-DAC was applied for the removal of hexavalent chromium (Cr(VI)) ions from water, where the efficiency was evaluated as functions of the initial chromium concentration, adsorption time, pH value, and co-existing anions. It was found that all c-DAC samples showed excellent adsorption efficiencies against Cr(VI), where the c-DAC with the highest charge density exhibited the maximum adsorption capacity of 80.5 mg/g. The Cr(VI) adsorption mechanism is found to be dominated by the electrostatic interactions between the quaternary ammonium cations on the c-DAC surface and Cr(VI) ions and can be best described using the Langmuir model. These samples also exhibited stable adsorption capacity in a wide pH range, where the c-DAC surface could remain positively charged.
Keywords: cationic nanocellulose; Girard's reagent T; adsorption; chromium removal; water treatment; biodegradable adsorbent